Synopsis of the Colombian Stag Beetles: A baseline for conservation assessments - Juan Sebastián D. Cáceres; Indiana Cristóbal Ríos-Málaver; Jennifer C. Girón (Caldasia)
Stag beetles, or Lucanidae (Insecta: Coleoptera: Scarabaeoidea), are among the most charismatic groups of scarab beetles. However, their ecology and natural history are largely unknown, partly due to their rarity in the field and in biological collections. This contribution summarizes the status of knowledge of the Colombian Lucanidae, based for the most part in bibliographic research and personal observations from fieldwork and biological collections in Colombia and Brazil. Bibliographic records are supplemented by data from the Global Biodiversity Information Facility (GBIF), including field obser-vations recorded through the online platform iNaturalist. In the literature, we found 19 species of stag beetles recorded for Colombia, belonging to five genera, three tribes, and two subfamilies. Bibliographic records are concentrated in the Andean region of Colombia, with some records in the Caribbean and Pacific regions. The lowlands of the Amazon and Orinoco regions lack any records for lucanid beetles. The diversity and ecology of stag beetles in Colombia are discussed in the light of current environmental threats. By presenting diagnoses and an identification key to the lucanid genera present in the country, along with known distributional data, and a discussion about their ecology, this contribution constitutes the first step towards proposing Colombian lucanids as species in need of conservation efforts.